Analysis of islamic banking financial performance before, during and after global financial crisis - Rifqi Muhammad; Condro Triharyono (Jurnal Ekonomi & Keuangan Islam, 2019)
The purpose of this study is to analyze the difference of the financial performance of Islamic banking before, during, and after global financial crisis. This study uses CAMEL ratios which consist of Capital, Asset quality, Management, Earning, and Liquidity ratio. The samples are Islamic banks in South-East Asia and East Asia using secondary data from financial statements of those Islamic banks before (2006-2007), during (2008), and after (2009-2010) global financial crisis. This study examines the hypotheses using Analysis of Variance (ANOVA) as analytical tool. This result shows that there are differences performance on the variables of capital, asset quality, management and earning measured by return of asset (ROA) while earning measured by operating expense ratio (OER) and liquidity do not indicate any differences in financial performance during the period. Thus, banks need to strengthen their liability side during a financial crisis.